Los clasificadores de posesión en wichí - Cayré Baito, Lorena (2010)
The aim of this paper is to analyze the possessive classifiers ka, lo and ko of the Wichí language. In the Wichí reviewed literature, only ka and lo have been described and studied. This article describes, compares and analyzes the morphosyntatic characteristics, compatibilities and notions of possession of the three classifiers according to Heine’s (1997) approach. The following hypothesis is proposed here: a possession scale in which, on the one hand, possessive constructions with ko and lo express permanent possession (in the sense that the possessor it is always, in some way, related to the possessed item; therefore it is possible to affirm that such an item belongs to that possessor). On the other hand, possessive constructions with ka express temporal and/or physical possession as well as permanent possession; but in this case, the possessed item may belong to the possessor or not.